Adipokinetic hormones control amylase activity in the cockroach (Periplaneta americana) gut. (5th April 2016) - Bodláková, Karolina; Jedlička, Pavel; Kodrík, Dalibor
Abstract: This study examined the biochemical characteristics of α‐amylase and hormonal (adipokinetic hormone: AKH) stimulation of α‐amylase activity in the cockroach ( Periplaneta americana ) midgut. We applied two AKHs in vivo and in vitro, then measured resultant amylase activity and gene expression, as well as the expression of AKH receptor ( AKHR ). The results revealed that optimal amylase activity is characterized by the following: pH: 5.7, temperature: 38.4 °C, K m (Michaelis–Menten constant): 2.54 mg starch/mL, and V max (maximum reaction velocity): 0.185 μmol maltose/mL/min. In vivo application of AKHs resulted in significant increase of amylase activity: by two‐fold in the gastric caeca and 4–7 fold in the rest of the midgut. In vitro experiments supported results seen in vivo : a 24‐h incubation with the hormones resulted in the increase of amylase activity by 1.4 times in the caeca and 4–9 times in the midgut. Further, gene expression analyses reveal that AKHR is expressed in both the caeca and the rest of the midgut, although expression levels in the former were 23 times higher than levels in the latter. A similar pattern was found for the amylase ( AMY ) gene. Hormonal treatment did not affect the expression of either gene. This study is the first to provide evidence indicating direct AKH stimulation of digestive enzyme activity in the insect midgut, supported by specific AKHR gene expression in this organ.